The Perturbation Encompassing Dental Amalgam Toxicity: A Review - Arjun Hegde1 , Ganaraj Shetty2 , Nishi Jayasheelan3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Amalgam in dentistry has been in use for over 150 years and still been widely used because of its low cost,easy application, durability, bacteriostatic effect, and strength. Whenever aesthetics isn’t the prime concernit is possibly used with no age bar, in areas of stress, as a foundation for cast-metals, ceramic restorations,and below-par oral hygiene conditions. Its advantages such as long-lasting and being less technique sensitiveamong all restorative materials, there has been growing concern about amalgam that it causes mercurytoxicity. Mercury (Hg) has been historically popular as one of the extremely toxic nonradioactive materials.Therefore, the present article aims to discuss and assess a brief historical review of literature on its adverseeffects, toxicological aspects that have been noted, potential risks relating to the dental personnel’s and itssafe and effective way of manipulating and handling concerning the use of mercury in dentistry.